The Rise of Brand Love and E-Vocacy in Electric Vehicle Marketing – A Systematic Review - Leo, Gundur; Sutrisno, Rivan; Sakova, Megha (Journal of Consumer Studies and Applied Marketing, 2025)
As the electric vehicle (EV) sector shifts from a niche to a mass market, traditional cognitive-based marketing models are inadequate for explaining deep consumer loyalty. This Systematic Literature Review (SLR) synthesizes the evolution of green marketing stimuli and their impact on consumer advocacy. Adhering to PRISMA guidelines, we analysed 33 high-impact empirical studies (2020–2025) to construct an enhanced Stimulus-Organism-Response (S-O-R) framework integrated with Signalling Theory. The results reveal three critical paradigm shifts. First, generic "Green Marketing" has evolved into specific, high-efficacy signals: Green Innovation (competence), Green Transparency (integrity), and Eco-Prestige (status). Second, the analysis identifies a "Satisfaction Trap," demonstrating that Green Brand Love—an intense emotional attachment—is a significantly stronger predictor of high-value behaviors than cognitive satisfaction. Third, consumer loyalty has shifted from passive repurchase intention to Active Evangelism and E-Vocacy (Electronic Advocacy). The study proposes an Integrated Green Signaling Model that positions Green Trust as a cognitive gateway to Green Brand Love, moderated by Tech-Anxiety. This framework advances prior S-O-R models by explicitly linking signalling efficacy to affective pathways, offering a robust theoretical roadmap for future research in developing markets characterised by infrastructural constraints.